Forms and Distribution of Phosphorus along A Toposequence at the University of Benin, Nigeria (American Journal of Geospatial Technology, 2024)
The experiment was conducted at University of Benin, Nigeria, involving soil samples from four toposequence sites (Crest, Middle, Lower, and Bottom) at different depths (0-15 cm, 15-30 cm, and 30-45 cm). A total of 36 samples were collected and analyzed for various parameters using standard procedures. The parameters included particle size distribution, pH, total organic carbon (TOC), total nitrogen (N), available phosphorus (P), Carbon (C), Hydrogen (H), Magnesium (Mg), Potassium (K), Sodium (Na), ECEC, and Aluminum (Al). Results indicated that pH was lowest in the Crest area (pH 4.10 at 30-45 cm depth) and highest in the Bottom area (pH 5.80 at 0-15 cm to 30-45 cm depth). Different soil properties showed varying highest values across the toposequence depths. These properties included Total organic C, Total N, Available P, Ca, K, Mg, H, Na, ECEC, sand content, and the various forms of phosphorus. The correlation table revealed significant positive and negative relationships between different forms of phosphorus and various soil physical and chemical properties. The experiment demonstrated distinct variations in soil properties along the toposequence sites and depths. The findings contribute to a better understanding of soil characteristics in the studied region, aiding in informed agricultural practices and land management decisions.